Kemampuan Berpikir Analitis Masalah Bangun Ruang Ditinjau Dari Gaya Kognitif - Pratiwi Viyanti; Mumtahana, Lusia; Aryanto, Sherif Juniar (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
The ability to think analytically is a student's skill when describing a problem so that several parts of the problem are formed and also determining relationships based on ongoing problems. Different cognitive styles in obtaining results both visually and verbally will form two groups, namely the visualizer cognitive style and the verbalizer cognitive style. Researchers use the visualizer and verbalizer cognitive styles in order to find out students' analytical thinking abilities when determining problems in an image or word. This research is a qualitative descriptive research. The topics used were 3 students who had a visualizer cognitive style and 3 students who had a verbalizer cognitive style for class V MI Maarif Buduran. The results obtained are students' analytical thinking skills who have a visualizer cognitive style in the indicator category when understanding problems, planning solutions, carrying out solutions, and re-examining the results of solutions. Meanwhile, visualizer students are classified as sufficient indicators to explain the relationship between the strategy used and the problem that must be solved. Students who have a visualizer cognitive style tend to use images to solve mathematical problems. For students, the cognitive verbalization style is classified as good in all indicators of the level of understanding the problem, planning a solution, carrying out the solution, and reviewing the results of the solution, except for the part that summarizes the problem and conclusions.